2020 IEEE 70th Electronic Components and Technology Conference (ECTC) 2020
DOI: 10.1109/ectc32862.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Packaging and System-Integration Platform with Integrated Antennas for Scalable, Low-Cost and High-Performance 5G mmWave Systems

Abstract: In this work, we present a novel packaging and system-integration platform with integrated antennas (antenna-in-package, AiP, platform) for 5G millimeterwave (mmWave) systems. We illustrate the application of the platform for the development of miniaturized, scalable, low-cost and high-performance 5G mmWave systems for new radio (NR) base stations. RF characterization of the dielectric material of the platform and the integrated mmWave antennas as well as thermal investigations of the platform are presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Growth of GaN on Silicon substrates is now widely practiced. Recent work has shown that CMOS-like processing can be done with GaN-on-Si to produce nitride-based ICs, followed by wafer bonding to CMOS ICs [147]. It can be anticipated that if sufficient market demand develops, heterogenous integration will become cost-effective such that PA designers can explore benefits of both CMOS and III-V technologies in their solutions.…”
Section: A Power Efficiency and Bandwidth Limiting Factors For High Mm-wave Frequency Pasmentioning
confidence: 99%
“…Growth of GaN on Silicon substrates is now widely practiced. Recent work has shown that CMOS-like processing can be done with GaN-on-Si to produce nitride-based ICs, followed by wafer bonding to CMOS ICs [147]. It can be anticipated that if sufficient market demand develops, heterogenous integration will become cost-effective such that PA designers can explore benefits of both CMOS and III-V technologies in their solutions.…”
Section: A Power Efficiency and Bandwidth Limiting Factors For High Mm-wave Frequency Pasmentioning
confidence: 99%
“…In recent years, with the transformation of mobile communication networks, more and more research has been conducted on the frequency bands of millimeter wave communication systems, including n257 (26.5-29.5 GHz), n258 (24.2-27.5 GHz), n259 (39.5-43.5 GHz), n260 (37-40 GHz), and n261 . Implementing highperformance, low-cost, and low-power transceivers has become an important research topic [6]. In addition to the above frequency bands, scientists are also actively studying the 60 GHz and 77 GHz communication frequency bands and applying them in the fields of industry, medical treatment, and automotive radar [7].…”
Section: Introductionmentioning
confidence: 99%
“…5G wireless communication networks have already been developed and are expected to dramatically reshape the wireless communication landscape. Nevertheless, a number of technical challenges still need to be addressed in the most recent packaging development approaches, such as the implementation of a large number of connections at high data rates, exhibiting high gain to compensate for the high free space loss at millimeter wave frequencies [12]. In particular, in Serena project, PCB embedding technology offers the potential to realize an integrated RF electronics module containing ICs for RF signal generation and antennas with very short interconnects in a single package, thus minimizing the signal path losses.…”
Section: Introductionmentioning
confidence: 99%